Is body mass index associated with symptom severity and health-related quality of life in irritable bowel syndrome?: a cross-sectional study - Dong, Yuanjun; Berens, Sabrina; Eich, Wolfgang; Tesarz, Jonas (BMJ open, 2018)
Objective: The aim of this study was to describe the body mass index (BMI) distribution in patients with irritable bowel syndrome (IBS) based on the Rome III criteria and to evaluate the association of BMI with symptom severity and quality of life (QOL). Methods: A cross-sectional study was carried out in patients visiting our outpatient functional gastrointestinal disorders specialty clinic. IBS diagnosis was made based on Rome III criteria. IBS symptom severity was investigated using the IBS severity score system. QOL was assessed using the Short Form 36 Health Survey, which consists of physical health and mental health. Results: 366 patients (252 women) who fulfilled Rome III criteria and provided complete BMI data (23.90±5.22 kg/m2) were included. Overall, 59.0% of patients with IBS were in the normal weight range, 30.3% were overweight or obese, and 10.7% were underweight. Both physical and mental health decreased significantly with the severity of symptoms (all p<0.01), while controlling for several covariates (age, gender, family status, education status and IBS subtypes). Obesity and symptom severity (β=−0.177,△R2=0.037, p<0.01; β=−0.387,△R2=0.147, p<0.01) were significant negative factors that influencing physical health. Symptom severity (β=−0.301,△R2=0.084, p<0.01) was significant negative factor that influencing mental health. However, BMI didn’t account for additional variance in mental health (p>0.05). Conclusion: Being overweight is a common phenomenon in patients with IBS regardless of IBS subtype. The association between QOL and symptom severity followed a negative dose-response pattern. Patients with higher BMI, especially obese patients, were more frequently in poor physical health. However, this kind of relationship was not found in BMI and mental health.